Physical layer security for wireless sensing and communication - Arslan, Hüseyin, 1968-; Furqan, Haji M. (IET security series ;, 2022)
Wireless physical layer (PHY) security has attracted much attention due to the broadcast nature of the wireless medium and its inherent vulnerability to eavesdropping, jamming, and interference. Physical Layer Security for Wireless Sensing and Communication covers both communication and sensing security from a broad perspective. The main emphasis is on PHY security, although other security measures are covered for the sake of completeness and as a step towards cross-layer security and cognitive security vision. After discussing the features of wireless channels from both the communication and sensing perspectives, the book details their exploitation for secure transmission utilizing various approaches. Wireless sensing and radio environment concepts are also addressed, along with the related security implications in terms of eavesdropping, disruption, manipulation, and, in general, the exploitation of wireless sensing by unauthorised users. Several solutions for these threats from the domains of wireless communication, military radars, and machine learning, are discussed. The book provides valuable information to researchers in academia and industry, as well as engineers, developers, and advanced students in the field of cybersecurity.